Pengaruh Media Kahoot terhadap Minat Belajar PAI Siswa Kelas IV di SDN 15 Sutijo - Rizki, Arif Aulia; Dafirsam, Dafirsam; Arifmiboy, Arifmiboy (MASALIQ, 2025)
This study aims to determine the effect of Kahoot media on Islamic Religious Education (PAI) learning interest of fourth grade students at SDN 15 Sutijo. The background of this study is the students' low interest in learning, which is shown by behaviors such as playing during learning, disturbing friends, leaving class, and sleeping in class. Although teachers have tried various innovations, the methods used have not succeeded in attracting students' attention. This study used a quantitative experimental approach with a pretest-posttest single group design. The study population consisted of 28 fourth grade students of SDN 15 Sutijo, which also became the sample through the total sampling technique. Data were collected using questionnaires and analyzed using paired sample t-test. The results showed that Kahoot media had a significant effect on increasing students' interest in learning. This is evidenced by the sig value of 0.002 (<0.05) and the t value of 3.418, greater than the t table of 2.052 (t> t table). Thus, Kahoot media is proven to be able to create interesting and effective learning to increase students' interest in learning PAI subjects.